Legal Protection for Refugees Without Identity from Country of Origin - nurainun nurainun; Raditya Afrisal Hidayat; Moh. Syaifur Rijal; Dennis Darmawan Jo; Petrus Avelino Framayuka Tolang (Hang Tuah Law Journal, 2020)
Currently refugee issues have become a concern for every country. It was marked by the existence of the 1951 Refugee Convention to overcome this problem. However, Indonesia is not a party to that Convention, there is no article mention about refugees’ permits in Immigration Law. To grant their own status are the authority of UNHCR through their representatives who are placed in the Immigration Office. When refugees are crossing the countries without carrying identity cards these refugees are arrested by the State security apparatus. The method used in this study is a normative juridical research method. The results of this study indicate that the permits for refugees is not known in the Immigration Act, it does not mean that Indonesia can expel refugees to their home countries. Where refugees must be protected by all countries.